Changing Furrow Irrigation to Increase Efficiency and Feasibility Study of Reusing Surface Runoff - Ehsan Dayer; Ebrahim Pazira; Heydar Ali Kashkuli; Hossein Sedghi (Salehan Institute of Higher Education, 2017)
To improve irrigation techniques and the utilization of available water resources in Iran, a first steps re evaluation of traditional irrigation methods. To assess the efficiency of furrow irrigation, a 4-ha plot (87 furrows) cultivated with sugarcane was evaluated in Khuzestan Province. The quantities of inflow, outflow runoff, soil moisture before irrigation, depth of root development and depth of water infiltration were measured and thus the values of water use efficiency, uniformity coefficient, and distribution uniformity were determined for the selected plot. Using Geographical Information System, in ArcView, the irrigation efficiency of its levels were analyzed using two furrow irrigation methods: open and closed-end. The results showed that the irrigation efficiency, uniformity coefficient and distribution uniformity for the open-end than the closed-end method. The prevention of deep infiltration losses (approximately 30% lower than for closed-end) and allowing outflow of end runoff, and depending on water quality, the riffle can be considered ideal for irrigating other surfaces.